Less is more: Silver-AIE core@shell nanoparticles for multimodality cancer imaging and synergistic therapy. (April 2020) - He, Xuewen; Peng, Chen; Qiang, Sujing; Xiong, Ling-Hong; Zhao, Zheng; Wang, Zaiyu; Kwok, Ryan T.K.; Lam, Jacky W.Y.; Ma, Nan; Tang, Ben Zhong
Abstract: Nanomaterials with integrated multiple imaging and therapeutic modalities possess great potentials in accurate cancer diagnostics and enhanced therapeutic efficacy. Traditional strategies for achieving multimodality nanoplatform through one by one combination of different modalities are challenged by the complicated structural design and fabrication as well as inherent incompatibility between different modalities. Herein, a novel strategy is presented to realize multimodal imaging and synergistic therapy using a class of simple silver core/AIE (aggregation-induced emission) shell nanoparticles. In addition to the intrinsic AIE fluorescence (FL) and metal-based computed tomography (CT) and radiation therapy (RT) properties, an extra functionality at the core/shell interface was identified to enable excellent photothermal (PT) and photoacoustic (PA) performance. As a result, five imaging and therapy modalities (FL, CT, PA, photothermal therapy (PTT), and RT) were achieved with a single structural unit for sensitive tumor imaging and effective therapy. Graphical abstract: A "less is more" strategy is presented to realize multifunctionality within a simple silver core/AIE shell nanoparticle. Apart from their intrinsic AIE fluorescence and noble metal based computed tomography properties, an extra interface with excellent photothermal and photoacoustic functionalities was in situ generated between the core and shell part, enabling multimodality tumor imaging and synergistic therapy. Image 1